Comparative evaluation of edible films impregnated with sage essential oil or lactoperoxidase system: Impact on chemical and sensory quality of carp burgers. Issue 9 (18th June 2019) - Ehsani, Ali; Hashemi, Mohammad; Aminzare, Majid; Raeisi, Mojtaba; Afshari, Asma; Mirza Alizadeh, Adel; Rezaeigolestani, Mohammadreza
Abstract: The aim of this study was to examine alginate (AL), chitosan (CH), and gelatin (ZH) films incorporated with Salvia officinalis essential oil (SOE) or lactoperoxidase system (LPS) for their antioxidant characteristics, and their effects on main chemical spoilage parameters (Total volatile basic nitrogen [TVB‐N], thiobarbituric acid reactive substances [TBARs], peroxide value [PV], and free fatty acids [FFA]), and sensorial characteristics of refrigerated carp burgers. A good correlation was observed between total phenolic content and DPPH radical scavenging activity of the developed films. Among the active composites, the minimum TVB‐N (10.61 mg/100 g), TBARs (3.11 mg of malonaldehyde/kg), and FFA (5.34% of oleic acid) values were recorded for the samples treated with CH/LPS, on the final day of storage, while gelatin films were least effective. Sensory evaluation revealed that the burgers treated with active CH and AL films received better scores, especially for odor and overall acceptability attributes, compared to untreated control sample. Practical applications: This manuscript addresses an important area in active food packaging by developing and comparing bioactive edible films based on natural ingredients. Biodegradable active films were developed based on alginate, chitosan, and gelatin with sage essential oil and lactoperoxidase system. Considering all the health concerns related to synthetic chemical preservatives, the potential relevance of using these newly packaging films in foods products was emphasized. This manuscript will be of interest to food science researchers from the perspective of presenting natural‐based packaging films for extending foods shelf life.